Microbiological safety of commercial canned and dry pet food products in Lebanon - Serhan, Mireille; Hadid, Michella; Dimassi, Hani; Deghel, Maria; Hassan, Hussein F. (Frontiers in Veterinary Science, 2022)
Estimating the microbiological quality of pet food is essential in providing healthy and safe foods to pets. The aim of this study was to assess the microbiological safety of pet food marketed in Lebanon, namely cat and dog products. To the best of our knowledge, no studies have been conducted in Lebanon nor the Middle East region with reference to pet food quality. Lebanese market was screened and a total of 165 dry and canned pet food products were identified, collected and analyzed for their load of total aerobic microbial count, Enterobacteriaceae species, yeasts and molds, and for the presence of Salmonella and Listeria species. Dry pet food products had higher contamination level compared to canned ones. In terms of non-conformity to the European commission regulations, out of the 165 brands, 11 (7%) had a total aerobic microbial count above 106 cfu/g, and 27 (16%) exceeded 3×102 cfu/g as a maximum limit of Enterobacteriaceae. Among the dry brands, 8 out of 66 (12%) had a contamination level of yeasts and molds above 104 cfu/g. Salmonella was detected in 68 (41%) and Listeria in 106 (64%) of brands. These alarming results necessitates setting and monitoring microbiological standards for pet food in Lebanon. This study contributes as well to the building of a database for knowledge development regarding the potential contamination of pet food by the abovementioned microorganisms.